Isolation and Characterization of Indigenous Lipase Producing Bacteria from Lipid?rich Environment - Aktar, Lovely; Khan, Farhana Islam; Islam, Tahmina; Mitra, Shawon; Saha, Mihir Lal (Plant Tissue Culture and Biotechnology, 2016)
To isolate and characterize lipase producing bacteria from lipid?rich environment and screen the best lipolytic indigenous bacteria a study was made. For the isolation of bacteria, oil based wastewater and soil were collected from ten different sampling sites. Four different media were used for study the aerobic heterotrophic bacterial count. The highest bacterial count (1.56 × 107 cfu/gm) was observed in dairy farm soil and lowest (8.3 × 102 cfu/ml) in the Buriganga river water. The highest percentage (94.51) of lipase producing bacteria was found in edible oil mill soil and lowest (23.44) in the Buriganga river water. Among the total isolates 30 showed better lipase activity. Potential ten lipase producers were taken for molecular identification. Among them, nine genera were matched with their conventional identification but conventionally identified Acetobacter liquifaciens was found to be as Stenotrophomonas maltophilia. The enzyme produced by the isolated bacteria could be used for the treatment of lipid?rich wastewater. Plant Tissue Cult. & Biotech. 26(2): 243-253, 2016 (December)